Development of biology module based on discovery learning and ethnoscience to improve students’ science literacy - Khairunisa, K.; Violita, V.; Arsih, Fitri; Chatri, Moralita; Anhar, Azwir; Fransisca, Rozalia (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Indonesian students' low scientific literacy, caused by limited culturally contextual learning and materials, highlights the need for improvement. This study aims to develop a valid, practical, and effective biology learning module based on discovery learning integrated with ethnoscience, as an effort to improve students' science literacy skills. The type of research used is research and development (R&D) using the Plomp model. The research subjects are 10th-grade students at SMA Negeri 2 Bukik Barisan. The instruments used were validity sheets, practicality sheet, and science literacy test questions. Validation of science literacy questions using ANATES Ver. 4.0 with a validity score of 0.74 (high category) and reliability of 0.85 (high category). The research data were analysed using validity tests, practicality tests, t-tests, and N-Gain Score tests. The results of the study indicate that the developed product, which is a biology learning module based on discovery learning integrated with ethnoscience, meets the criteria of being highly valid, highly practical, and effective in improving students' science literacy skills from the aspects of context, content, and scientific process. The results of this study can be used as a reference for teachers in integrating ethnoscience into 21st-century learning to develop students who have scientific literacy and are grounded in local wisdom.